Symptomatic hyponatremia: A consequence of acute urinary retention due to benign prostatic hyperplasia - Manappallil, Robin George; Chally, Roy; Josephine, Blessy (Indian Journal of Case Reports, 2019)
Hyponatremia is a common disorder in the geriatric population. Patients can present in altered sensorium, seizures, and even coma. Syndrome of inappropriate antidiuretic hormone secretion (SIADH) and diuretic therapy are the common causes in the elderly. However, acute urinary retention due to benign prostatic hyperplasia (BPH) resulting in hyponatremia is a rare scenario. Here, we report the case of a 60-year-old male patient who developed hyponatremia following urinary retention due to benign prostatic hyperplasia (BPH); which is a rare scenario.